PENGARUH PENGEMBANGAN KARIER DAN PELATIHAN KERJA TERHADAP TURNOVER INTENTION PEGAWAI - Zahara Tussoleha Rony; Dahlia Jelita (ITB AAS INDONESIA, 2023)
This study aims to determine simultaneously the effect of career development and job training on the employee turnover intention of PT. Mega Ocean Jaya, Indonesia, and knowing the effect of career development on turnover intention and job training on employee turnover intention of PT. Mega Ocean Jaya, Indonesia. The research method uses a quantitative approach. The population in this study are employees of PT. Mega Ocean Jaya totaled 72 respondents. The sampling method used purposive sampling. As for data analysis using descriptive statistics, Data Quality Test, Classical Assumption Test, Multiple Linear Regression Analysis, and Hypothesis Testing with SPSS IBM Statistics 26. Based on the study's results, it was found that career development variables influence turnover intention. It can be seen that the sig value is 0.000 ttable 1.994. The job training variable has an influence on turnover intention. It can be seen that the sig value is 0.006 ttable 1.994. From the results of the study, it was found that partially and simultaneously the two independent variables proved to have an effect on the turnover intention variable. Therefore, career development and job training facilities provided by the company to employees can minimize the level of turnover intention of PT. Mega Ocean Jaya.